The relationship between personality traits and anxiety/depression levels in different drug abusers' groups - Tatalović Vorkapić Sanja; Dadić-Hero Elizabeta; Ružić Klementina (Istituto Superiore di Sanità, 2013)
AIM: Since psychosocial characteristics of drug abuse involve mainly specific personality and emotional changes, it is very important to investigate characteristics of addictive personality in relationship with emotional state of the individual. Considering that, the objective of this study was to analyse the relationship between personality structure and emotional state of two different groups: heroin addicts and recreate drug abusers. METHODS: The total of 288 (219 males and 69 females; 191 heroin addicts and 97 recreate drug users) clients of Centre for the prevention and treatment of drug abuse in Rijeka completed Eysenck's Personality Questionnaire (EPQ R/A), Beck's Anxiety Inventory (BAI) and Beck's Depression Inventory (BDI). Their average age was 22. RESULTS: In the group of heroin addicts, higher levels of anxiety and depression were significantly correlated with higher levels of psychoticism, neuroticism, criminality and addiction. In the group of recreate drug users, higher extraversion and social conformity were determined. Furthermore, in the first group was found even higher depression. However when the anxiety level was compared between these two groups, there was no significant difference. CONCLUSION: Overall, the findings implied that the used measurement instruments could serve as the useful diagnostic tools that could ensure advantageous treatment directions.